Assimilated Uzbek Language Words and their Expression in Dictionaries - Nazarova, Dilnoza Gulomovna (European Journal of Life Safety and Stability (2660-9630), 2021)
We know that language is constantly evolving. He lives according to his own laws, develops, sorts according to the pattern of consumption, “archives the unnecessary”. When the time comes, he adopts new alternatives to certain units or builds other units based on his own internal capabilities. In our opinion, the power of language, which sometimes suppresses the human mind, and the fact that it is characterized by generality, essence, possibility and reason, is even more obvious here. Naturally, changes in social life, innovations in society, are primarily reflected in the language. After the Uzbek society gained national independence, radical changes in all spheres of public life, including education, medicine, economy, led to the introduction of new lexical units into the vocabulary of the Uzbek language. Therefore, some lexical units began to move from the active layer of the vocabulary of the Uzbek language to the inactive one, and a number of words and fixed connections, which until recently were inactive, moved to the active layer. To what extent was the Uzbek lexicography able to cover these processes? Do these processes not only increase the vocabulary of the Uzbek language, but also adversely affect the number of common Turkic words that form the basis of the national language? The article discusses the solution of these problems from the point of view of the development of the vocabulary of the Uzbek language over the years of independence.